COVID-19 vaccine hesitancy and acceptance in patients with multiple myeloma: A national multicenter survey in China - Huiwen He; Xianghong Jin; Ziping Li; Shuangjiao Liu; Wenming Chen; Wanling Sun; Baolai Hua; Yongzhe Li; Junling Zhuang (Asian Pacific Journal of Tropical Medicine)
Objective: To investigate factors influencing vaccine hesitancy and its effects on SARS-CoV-2 infection in multiple myeloma (MM) patients during the Omicron BA.4/5 subvariant outbreak. Methods: This cross-sectional study was conducted in mainland China from December 26, 2022, to April 20, 2023. An expert-developed anonymous online questionnaire was distributed via WeChat mini-program to several groups of 500 MM patients, each comprising of 500 patients. The questionnaire covered demographic characteristics, MM medical attributes, COVID-19 vaccine status, and clinical manifestations of COVID-19. Data were analyzed to assess the impact of vaccination on COVID-19 infection rates and the disease severity among MM patients. Results: Among 508 valid responses from 30 provinces, only 34.1% (n=173) of MM patients reported receiving COVID-19 vaccination, and the proportions were lower among patients who had undergone autologous stem cell transplantation (20.2% vs. 48.4%, P<0.001). Vaccine hesitancy was primarily attributed to physician recommendations (52.0%), conflicts with MM treatment (37.8%), and concerns about MM progression (31.3%). Hospitalization due to severe SARS-CoV-2 infections was significantly reduced in the vaccinated group (4.8% vs. 12.3%, P=0.038). Conclusions: The lower infection rate in MM patients may be attributed to stringent quarantine measures and self-imposed social restrictions. While vaccination did not directly correlate with fewer SARS-CoV-2 infections, it did afford protection to vulnerable populations. Clinicians are encouraged to recommend vaccines to MM patients to mitigate severe infections and associated mortality during recurrent COVID-19 waves.